Cost-Benefit Analysis of Soilless Cultivation System in Tagaytay City, Philippines - Tality, Dhapne; Serevo, Andrea Justine; Alipio, Alfonso Lucas; Rosete, Marie Antoinette (International Journal of Social and Management Studies, 2022)
The city of Tagaytay is a tourist destination that is mainly reliant on its agricultural center. As the area's commercialization grows, agricultural lands continue to decline, making agriculture's preservation increasingly challenging. Hydroponic farming is an optimal soilless cultivation method that can be presented as an alternative solution for this. This study conducted a cost-benefit analysis of an existing hydroponic farm in Tagaytay. Hydroponic farming does not require the same amount of arable land as traditional farming. Water usage is significantly less but the energy requirements may be higher though it is a more sustainable method in the long run. The findings of this study justified the feasibility of adopting hydroponic farming in the city of Tagaytay through examining the regional implications of the project as well as its environmental and social externalities.